The burden of Clostridioides difficile on COVID‐19 hospitalizations in the USA. Issue 4 (29th January 2023) - Sohal, Aalam; Chaudhry, Hunza; Singla, Piyush; Sharma, Raghav; Kohli, Isha; Dukovic, Dino; Prajapati, Devang
Abstract: Background and Aim: Clostridioides difficile infection (CDI) is the leading cause of hospital acquired‐infectious diarrhea in the USA. In this study, we assess the prevalence and impact of CDI in COVID‐19 hospitalizations in the USA. Methods: We used the 2020 National Inpatient Sample database to identify adult patients with COVID‐19. The patients were stratified into two groups based on the presence of CDI. The impact of CDI on outcomes such as in‐hospital mortality, ICU admission, shock, acute kidney injury (AKI), and sepsis rates. Multivariate regression analysis was performed to assess the effects of CDI on outcomes. Results: The study population comprised 1581 585 patients with COVID‐19. Among these, 0.65% of people had a CDI. There was a higher incidence of mortality in patients with COVID‐19 and CDI compared with patients without COVID‐19 (23.25% vs 13.33%, P < 0.001). The patients with COVID‐19 and CDI had a higher incidence of sepsis (7.69% vs 5%, P < 0.001), shock (23.59% vs 8.59%, P < 0.001), ICU admission (25.54% vs 12.28%, P < 0.001), and AKI (47.71% vs 28.52%, P < 0.001). On multivariate analysis, patients with CDI had a statistically significant higher risk of mortality than those without (aOR = 1.47, P < 0.001). We also noted a statistically significant higher risk of sepsis (aOR = 1.47, P < 0.001), shock (aOR = 2.7, P < 0.001), AKI (aOR = 1.55, P < 0.001), and ICU admission (aOR = 2.16, P < 0.001) in the study population. Conclusions: Our study revealed the prevalence of CDI in COVID‐19 patients was 0.65%. Although the prevalence was low, its presence is associated with worse outcomes and higher resource utilization.